The Application of Project-Based Learning as an Effort to Improve Learning Achievement in Vocational High School Students - Apolonio, Arya; Romas, Muslimah Zahro; Rizkiyana, Ria (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Low student achievement in vocational high schools (SMK) is one of the problems that has led to a decline in enrollment every year. One way to deal with this is to use a learning model that can boost student engagement and motivation. This study aims to investigate the relationship between project-based learning (PBL) and student academic performance at SMK. The researcher employed a quantitative approach with a sample size of 85 students out of a total population of 100 students. Data analysis was conducted using normality tests, linearity tests, Pearson Product Moment correlation tests, and partial correlation tests for each aspect. The normality test results showed that the data were normally distributed, while the linearity test showed a significant linear relationship between the two variables. Through the correlation test, the researcher found that there was a positive relationship between Project-Based Learning and learning achievement with a correlation coefficient of r = 0.572 and significant at the 0.01 level (p ≤ 0.05). These findings indicate that the implementation of Project-Based Learning significantly contributes to improving the learning achievement of vocational high school students. The implications of this study suggest that teachers need to optimize the use of project-based learning models as an effective learning strategy to improve the quality of learning and student learning outcomes in vocational high schools.Rendahnya prestasi belajar siswa di Sekolah Menengah Kejuruan (SMK) menjadi salah satu permasalahan yang berdampak pada menurunnya jumlah peserta didik setiap tahunnya. Salah satu upaya untuk mengatasi permasalahan tersebut adalah dengan menerapkan model pembelajaran yang mampu meningkatkan keaktifan dan motivasi belajar siswa. Penelitian ini bertujuan untuk mengetahui hubungan antara model pembelajaran berbasis proyek (Project-Based Learning) dan prestasi belajar siswa SMK. Peneliti menggunakan pendekatan kuantitatif dengan jumlah sampel sebanyak 85 siswa dari total populasi 100 siswa. Peneliti melakukan analisis data menggunakan uji normalitas, uji linearitas, dan uji korelasi Pearson Product Moment serta uji korelasi parsial pada setiap aspek. Hasil uji normalitas menunjukkan bahwa data terdistribusi normal, sedangkan uji linearitas menunjukkan adanya hubungan linier yang signifikan antara kedua variabel. Melalui uji korelasi, peneliti menemukan bahwa terdapat hubungan positif antara Project Based Learning dan prestasi belajar dengan nilai koefisien korelasi r = 0,572 dan signifikan pada tingkat 0,01 (p ≤ 0,05). Temuan ini menunjukkan bahwa penerapan Project Based Learning secara signifikan berkontribusi terhadap peningkatan prestasi belajar siswa SMK. Implikasi dari penelitian ini menunjukkan bahwa guru perlu mengoptimalkan penggunaan model pembelajaran berbasis proyek sebagai strategi pembelajaran yang efektif dalam meningkatkan kualitas pembelajaran dan hasil belajar siswa di SMK.